2018
DOI: 10.26773/smj.180609
|View full text |Cite
|
Sign up to set email alerts
|

Stature and Its Estimation Utilizing Arm Span Measurements of both gender Adolescents from Southern Region in Kosovo

Abstract: This study is based on measurements of Southern region Kosovan adolescents. The aim of this study was to examine the stature of adolescents from Southern region as well relationship between arm span and stature in both Kosovar genders. A total measured subject participated in this research was 225 out of which (105 girls and 120 boys), females average of age is 18.36±0.50 years old (range 18-20 years) and for male 18.40±0.55 years old (range 18-20 years).The anthropometric measurements were done by trained peo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 10 publications
(13 reference statements)
0
25
0
4
Order By: Relevance
“…All above-mentioned have confirmed the necessity for developing separate standing height models for each population on account of ethnic differences and the recent study conducted by Popovic and his collaborators who have analyzed the entire Kosovan population and have found specific correlation coefficient in Kosovan male (r=0.669) and female (r=0.625) population; however, some recent studies have also confirmed the regional differences between the same ethnic groups too Arifi et al, 2017b;Milasinovic et al, 2016a;2016b), which caused the need for additional caution. Therefore, the main goal of this research was to test the hypothesis if above-mentioned facts are true for the Western-Kosovans, that is, for the one of five Kosovan regions.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…All above-mentioned have confirmed the necessity for developing separate standing height models for each population on account of ethnic differences and the recent study conducted by Popovic and his collaborators who have analyzed the entire Kosovan population and have found specific correlation coefficient in Kosovan male (r=0.669) and female (r=0.625) population; however, some recent studies have also confirmed the regional differences between the same ethnic groups too Arifi et al, 2017b;Milasinovic et al, 2016a;2016b), which caused the need for additional caution. Therefore, the main goal of this research was to test the hypothesis if above-mentioned facts are true for the Western-Kosovans, that is, for the one of five Kosovan regions.…”
Section: Discussionmentioning
confidence: 90%
“…This region (Figure 1) covers the area of 2,494 square kilometers and has population of 368,907 inhabitants, while average density per square kilometer is 150 inhabitants (Komunat e Kosovës, 2013). Although Kosovo doesn't have too big territory, it has a very varied relief that mostly belongs to Dinarides range and the author assumed this fact might influence the main objective of this study, because of the type of the soil as well as other socio-economical and geographical characteristics as a potential influencing factors Arifi, Sermaxhaj, Zejnullahu-Raçi, Alaj, & Metaj, 2017b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the relationship of long bones and standing height was found to vary in diff erent ethnic and racial groups (Bjelica et al, 2012;Brown, Feng, & Knapp, 2002;Popovic, Bjelica, Georgiev, Krivokapic, & Milasinovic, 2016;Popovic, Bjelica, Molnar, Jaksic, & Akpinar, 2013;Popovic, Bjelica, Tanase, & Milasinovic, 2015;Masanovic, 2017;Reeves, Varakamin, & Henry, 1996;Steele & Chenier, 1990) as well as various regions (Arifi , 2013;Arifi et al, 2017b;Milasinovic, Popovic, Matic, Gardasevic, & Bjelica, 2016a;Milasinovic, Popovic, Jaksic, Vasiljevic, & Bjelica, 2016b). Hence, researchers have derived a specifi c formula for calculating standing height from long bones for each ethnic/race group.…”
Section: Relationship Foot Length/body Height In Eastern-kosovan Adolmentioning
confidence: 99%
“…Th is region (Figure 1) covers the area of 2,236 square kilometers and has population of 366,589 inhabitants, while average density per square kilometer is 255 inhabitants (Komunat e Kosovës, 2013). Although Kosovo doesn't have too big territory, it has a very varied relief that mostly belongs to Dinarides range and the author assumed this fact might infl uence the main objective of this study, because of the type of the soil as well as other socio-economical and geographical characteristics as a potential infl uencing factors (Arifi , 2013;Arifi , Sermaxhaj, Zejnullahu-Raçi, Alaj, & Metaj, 2017b).…”
Section: Introductionmentioning
confidence: 99%